Ressignificação e reapropriação social da natureza : práticas e programas de “convivência com o semiárido” no território de Juazeiro - Bahia - Carvalho, Luzineide Dourado (2010)
The context of this study is the reflexive relationship between nature and culture in contemporary times. The nature semiarid have received different understandings, guided by different rationales, and among these, the environment, which presents the proposal of 'Familiarity of the Brazilian Semiarid'. This proposal is understood as an idea-project that innovates, stimulates and directs the socio-environmental through social networks, graduating as a rhizome, weaving us through all its scales, welding different flags in the social struggles waged Semiarid contemporary (water, land, education and other claims). She leads the actors and social actors to social reappropriation of nature. These events are identified in the Territory of Juazeiro (Bahia), using three guidelines of 'familiarity': the democratization of the access to water and its programs (P1MC, P1 +2 and others), the democratization of ownership and regulation land (with emphasis on the situation of collective land to pasture Fund) and the sustainable use of biodiversity and agrobiodiversity Caatinga. It was examined whether these programs and practices reorient the use of natural resources, since not only meet the material support of the people, especially traditional rural communities, but also make up base intangible values of culture and identity associated with their territories of life and work. The theoretical foundation and methodological study of the phenomenological and cultural categories and geographic themes of nature, territory / territoriality, networks, and landscape. We analyzed how they are developing the new territoriality in the Semiarid by 'familiarity'. The phenomenon of 'familiarity' was perceived as a significant involvement of "be-like-the-other-in-the-wordl", from existentialism / worldliness of Heidegger, whose purpose was to describe the ontological sense of 'familiarity' in their actions mobilization and coordination, also anchored in the perception of Merleau-Ponty to understand the construction of a sense of hostility to nature and the deconstruction of these senses are transmuted into a kind of possibilities, using the analysis of documents and guidelines for network and the speech of the actors. The intention was to generate a careful look at the human condition in its worldliness semiarid backcountry, the ways in which it longs for 'familiarity' supplement their existence in their daily life, work and culture. It was considered that this search for resignation of nature, incorporates the redefinition of territorial identity hinterlands, evoked by the values of belonging and rootedness in the speeches, and practices in trade and exchange of knowledge between communities, institutions and networks. In the process of recovery of semiarid territory (physical and symbolic-cultural), we assessed that the "Education for familiarity', through the contextualization of knowledge, plays an important role in the process of intentional awareness of the subjects about their conditions of worldliness and generating a new look for themselves and their context (material and immaterial). A review of practices and programs of the 'familiarity' that allowed the learning of 'good use' of semiarid nature, through the ethics of prudence (the store) and contextualization, they have promoted reading as a territory Semiarid complex and multidimensional and generated the construction of new territoriality.